Predictors of Dental Fear and Anxiety in 9-12-year-old Children in Bosnia and Herzegovina - Elmedin Bajrić; Sedin Kobašlija; Amina Huseinbegović; Amila Zukanović; Nina Marković; Mediha Selimović-Dragaš; Amra Arslanagić; Lajla Hasić-Branković; Selma Zukić (University of Zagreb. School of Dental Medicine, 2022)
Objectives: Oral health in children is additionally burdened with the presence of dental fear and anxiety (DFA). These clinical psychologic entities in their progressive stages inevitably lead to avoidance of dental appointments, which makes prevention and therapy of oral diseases more difficult. Upon the onset of DFA in general, as one of the emotional outcomes of stress in a dental office, most children patients could define the specific stressors that were most intense for them, which could predict the presence of DFA. Aim: To examine the predictors of DFA presence in 9-12 year-old children, and investigate how they could explain the DFA occurrence in study participants. Material and Methods: The sample consisted of 200 children aged from 9 to 12 years. The DFA presence was determined by the modified version of the CFSS-DS scale. The child's behavior in the dental office during the treatment was evaluated by the trained observer using Venham anxiety and behavior rating scales. Socioeconomic status, characteristics of dental office visits, and previous caries experience were also analyzed. Results: The main DFA predictors were related to invasive dental treatments, where the behavior during dental treatment was the most accurate expression of the DFA appearance. Conclusions: Invasive dental procedures are the main stressful factor for DFA occurrence. Predisposing factors could strengthen the DFA occurrence.